THE EVALUATION OF PROMOTION STRATEGY OF MUSEUM BALI - Narita Astika Yapto; Francisca Titing Koerniawaty (Jurnal Ilmiah Hospitality Management, 2016)
The aim of this study was to evaluate of the promotion strategy of Museum Bali Puputan Badung, Denpasar, Bali, in order to increase the quantity of the visitors. The phenomenon of this study was lack of promotion which caused the quantity of the visitors have not reached the target yet. The promotion strategies used five variables of marketing mix such as advertising, personal selling, sales promotion, public relation and direct marketing. This is a qualitative descriptive study using the purposive technique and snowball sampling by interviewing personnels at Museum Bali. The data was analyzed using the SWOT analysis by crating promotion mix strategy formulation. The result of this study from the plan of the matrix combination quantitative strategy showed that Museum Bali needed to utilize the SO strategy that has the highest score was 6.34, the ST strategy was 5.65, the WO strategy was 2.49 and the WT strategy 1.80, with the effective formulation strategy was SO. It showed that attractiveness of the Museum Bali has strengths and opportunities so that can be utilized the existing of the opportunities. The strategy should be applied in this condition is to support the growth of the aggressive policy (growth oriented strategy).